Niektóre problemy nowelizacji polskiego prawa o ubezwłasnowolnieniu: [Problems of implementation of the Convention on the Rights of persons with disabilities in the Polish civil law] (Studia Prawnicze / The Legal Studies, 2013)
Celem niniejszego opracowania jest przedstawienie niektórych problemów, przede wszystkim w zakresie materii cywilnoprawnych, jakie rysują się przed ustawodawcą, który zamierza implementować postanowienia art. 12 Konwencji o prawach osób niepełnosprawnych.Procedura ratyfikacji przez Polskę Konwencji ONZ z dnia 13 grudnia 2006 r. o prawach osób niepełnosprawnych była bardzo istotnym, a być może przesądzającym czynnikiem podjęcia prac nad nowelizacją polskich przepisów o ubezwłasnowolnieniu.Należy tu zaznaczyć, że nowelizacją powinny być objęte nie tylko przepisy o ubezwłasnowolnieniu, lecz także inne przepisy prawa cywilnego o zdolności do czynności prawnych osób dorosłych oraz przepisy o pieczy nad osobami dorosłymi nie mogącymi samodzielnie prowadzić swych spraw. The article discusses the problems of implementation of the Convention on the Rights of persons with disabilities in the Polish civil law. Polish legislator needs to choose the model of legal regulation of adult’s protection, which will replace the incapacitation. The article presents the solutions adopted in this field in Germany, Austria, Switzerland, England, France, Hungary, and in some other European countries. The institution of incapacitation is deeply rooted in the Polish legal system, both in law and in legal culture. The abolition of incapacitation will require changes in many areas of law such as family law, rights of the patient, the rules of the exercise of the legal professions and the medical professions, and others. The reform of adult’s protection law carried out in other European countries have faced many problems, such as rising costs of institutions dealing with the protection and the ineffectiveness of many of the new norms. The reform of the law to protect adults conducted in Poland can and should learn from the experience of other countries in this regard.